Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Yang Tercatat dI IDX 30 - Fredi Eko Setiawan; Wahyu Dwi Warsitasari (Universitas 17 Agustus 1945, 2023)
This study aims to determine the effect of Profitability, Capital Structure, Company Size, Company Growth on company value in companies listed on the IDX30 Index. The research period is 2019 – 2021. This research uses a quantitative approach with a sampling technique using a purposive sampling method, so that 21 companies are obtained as research samples. The data analysis technique used in analyzing data uses Eviews 9.0. The results of this study indicate that partially Profitability has a significant effect on firm value. Capital structure has no significant effect on firm value. Firm size has a significant effect on firm value. Company growth has no significant effect on firm value. The results of this research simultaneously show that profitability, capital structure, company size, and company growth have a significant effect on firm value.